INVESTIGATION OF THE EFFECT OF MOBBİNG EXPOSURE LEVELS ON ORGANIZATIONAL COMMITMENT LEVELS OF TEACHERS AT SPORT HIGH SCHOOLS - Özdemir, Muhammed Said; Uğurlu, Fatih Mehmet (Nigde Omer Halisdemir University, 2021)
The main aim of this study is to decipher the relationship between mobbing exposure levels and organizational commitment levels of teachers in sports high schools, and to decipher whether there are significant differences between mobbing exposure levels and organizational commitment levels of teachers.For this purpose, "Mobbing Scale for Teachers" developed by Tanhan and Çan and "Organizational Commitment Scale" developed by Balay were used in this study. In the questionnaire form prepared, besides the scale expressions, questions including socio-demographic characteristics of the participants were also included. The sample group of the study consists of 101 teachers working in sports high schools in Elazığ, Diyarbakır, Muş, Bitlis, Siirt, Van and Tunceli provinces during the 2019-2020 academic year. In the process of obtaining the data set for the study, the survey method was used, and the SPSS 25.0 package program was used in the analysis of the data obtained. As a result of the analysis findings applied; It was determined that teachers' gender, education level, staff status and current working time in the institution caused statistically significant differences in terms of organizational commitment and exposure to mobbing. On the other hand, it was determined that the marital status of the teachers, the age group and the time they spent in their profession did not cause statistically significant differences in terms of their organizational commitment and exposure to mobbing. When the relationship between the levels of exposure to mobbing and organizational commitment of teachers working in sports high schools was examined, it was determined that there were negative significant relationships.

Bu çalışmanın temel amacı, spor liselerinde görev yapmakta olan öğretmenlerin mobbinge maruz kalma düzeyleri ile örgütsel bağlılık düzeyleri arasındaki ilişkinin incelenmesi olup, ayrıca öğretmenlerin mobbinge maruz kalma düzeyleri ile örgütsel bağlılık düzeyleri arasında anlamlı farklılıkların var olup olmadığının belirlenmesidir. Bu amaçla bu çalışmada, Tanhan ve Çan (2009) tarafından geliştirilen ‘’Öğretmenlere Yönelik Yıldırma Ölçeği’’ ile Balay (2000) tarafından geliştirilen ‘’Örgütsel Bağlılık Ölçeği’’ kullanılmıştır. Hazırlanan anket formunda, ölçek ifadelerin yanı sıra katılımcıların sosyo demografik özelliklerini içeren sorulara da yer verilmiştir. Araştırmanın örneklem grubunu ise 2019-2020 eğitim öğretim yılı içerisinde Elazığ, Diyarbakır, Muş, Bitlis, Siirt, Van ve Tunceli illerindeki spor liselerinde görev yapmakta olan 101 öğretmen oluşturmaktadır. Çalışmaya ilişkin veri setinin elde edilmesi sürecinde anket yöntemi uygulanmış olup, elde edilen verilerin analizinde ise SPSS 25.0 paket programından yararlanılmıştır. Uygulanan analiz bulguları neticesinde; öğretmenlerin cinsiyet, eğitim düzeyi, kadro durumu ve şu an ki kurumda çalışma süresinin örgütsel bağlılık ve mobbinge maruz kalma durumları açısından istatiksel olarak anlamlı farklılıklara neden olduğu belirlenmiştir. Buna karşın öğretmenlerin medeni durumu, yaş grubu ve mesleklerinde geçirdikleri sürenin örgütsel bağlılıkları ve mobbinge maruz kalma durumları açısından istatiksel olarak anlamlı farklılıklara neden olmadığı tespit edilmiştir. Spor liselerinde görev yapmakta olan öğretmenlerin mobbinge maruz kalma düzeyleri ile örgütsel bağlılık düzeyleri arasında ilişki incelendiğinde ise negatif yönlü anlamlı ilişkilerin var olduğu belirlenmiştir.
SPOR LİSELERİNDE ÇALIŞAN ÖĞRETMENLERİN MOBBİNGE MARUZ KALMA DÜZEYLERİNİN ÖRGÜTSEL BAĞLILIK İLE İLİŞKİSİNİN İNCELENMESİ
Keywords: Sports Medicine; Spor Hekimliği